A first‐in‐human pharmacodynamic and pharmacokinetic study of a fully human anti‐glucagon receptor monoclonal antibody in normal healthy volunteers. Issue 2 (14th September 2017) - Kostic, Ana; King, Thomas Alexander; Yang, Feng; Chan, Kuo‐Chen; Yancopoulos, George D.; Gromada, Jesper; Harp, Joyce B.
Abstract : Aims: Glucagon receptor (GCGR) blockers are being investigated as potential therapeutics for type 1 and type 2 diabetes. Here we report the safety, tolerability, pharmacokinetics (PK) and pharmacodynamics (PD) of REGN1193, a fully human glucagon receptor blocking monoclonal antibody from a first‐in‐human healthy volunteer randomized double‐blinded trial. Methods: Healthy men and women received single ascending doses of REGN1193 ranging from 0.05 to 0.6 mg/kg (n = 42) or placebo (n = 14) intravenously. Safety, tolerability and PK were assessed over 106 days. The glucose‐lowering effect of REGN1193 was assessed after induction of hyperglycaemia by serial glucagon challenges. Results: REGN1193 was generally well tolerated. There were small (<3× the upper limit of normal) and transient dose‐dependent increases in hepatic aminotransferases. No increase in LDL‐C was observed. Hypoglycaemia, assessed as laboratory blood glucose ≤70 mg/dL, occurred in 6/14 (43%) subjects on placebo and 27/42 (57%) on REGN1193 across all dose groups. All episodes of hypoglycaemia were asymptomatic, >50 mg/dL, and did not require treatment or medical assistance. Concentration‐time profiles suggest a 2‐compartment disposition and marked nonlinearity, consistent with target‐mediated clearance. REGN1193 inhibited the glucagon‐stimulated glucose increase in a dose‐dependent manner. The 0.6 mg/kg dose inhibited the glucagon‐induced glucose area under the curve for 0 to 90 minutes (AUC0‐90 minutes ) by 80% to 90% on days 3 and 15, while blunting the increase in C‐peptide. REGN1193 dose‐dependently increased total GLP‐1, GLP‐2 and glucagon, with plasma levels returning to baseline by day 29 in all dose groups. Conclusion: REGN1193, a GCGR‐blocking monoclonal antibody, produced a safety, tolerability and PK/PD profile suitable for further clinical development. The occurrence of transient elevations in serum hepatic aminotransferases observed here and reported with several small molecule glucagon receptor antagonists suggests an on‐target effect of glucagon receptor blockade. The underlying mechanism is unknown.